MODERNISASI ALAT TANGKAP DAN PENGARUHNYA TERHADAP NELAYAN TELUK PRIGI KAB TRENGGALEK TAHUN 1982-2006 - Nikmah, Khoirun (Institut Agama Islam Negeri Ponorogo, 2020)
This article aims to analyze the modernization of fishing gear and its influence on the Prigi Bay fishermen in Trenggalek Regency in 1982-2006. In the 1982-2006 temporal, Prigi Bay fishermen underwent several developments in fishing gear changes. Those who first used traditional fishing gear and then used more modern fishing gear. There are also fishermen who continue to use traditional fishing gear because of capital constraints.